An analysis of the modal function in the visual components of a graphic novel / Za’im Mohd Jais - Za’im, Mohd Jais (2019)
The introduction of graphic novels in Malaysian primary English classroom is seen as a great shift towards introducing multimodality. Due to its interplay of text and illustrations, graphic novels engage readers and increase their interest in reading. Hence, an analysis of visual components in the graphic novel and how they engage readers is worth exploring as these visual components distinguish graphic novel from other types of text. One graphic novel which is “The Jungle Book” was chosen as the main source of data as it is one of the compulsory texts to be introduced to primary school pupils in Malaysia under the Language Arts module. The visual components in “The Jungle Book” were identified and analysed based on the framework by Eisner (2008), McCloud (1994), Okum (2005) and McKenzie (2005). Then. the modal function of these visual components was analysed using O’Toole’s (1994) framework. Additionally, two interview sessions were held with two separate focused groups which comprise of pupils of differing proficiency in English; one group with intermediate to high level of proficiency and the other one with low proficiency. These interview sessions were aimed at validating the findings of the analysis of modal function which was done prior to the interviews. It is found that most of the visual components identified in the graphic novel “The Jungle Book” portray a high level of modal function which leads to a greater involvement of pupils towards the graphic novel. A few components are identified as less appealing to pupils based on the interview sessions. It is concluded that all visual components contribute to the realization of modal function where every component works simultaneously with each other to construe the intended meaning. This study is limited to only one graphic novel hence the findings could not be generalised to other graphic novels. However, it is a great platform for teachers to realize the benefits of utilizing graphic novels exhaustively in the classroom and for the authorities at the Ministry of Education Malaysia to take into consideration promoting graphic novel at a larger scale to achieve their prime objective of upholding the English Language in Malaysia.